Factors Influencing the Coverage of Complete Basic Immunization in Toddlers (Jurnal Ilmu Kesehatan Masyarakat, 2023)
The coverage of complete basic immunization is still low in the working area of Mentawai Regency, which is 59.8%. The national target achievement is 95%, indicating a gap of 35.2%. The aim of this research was to identify the factors influencing the completion of basic immunization. The research method used is analytical research with a cross-sectional study approach. The sample in this research consists of children aged more than 9 months until 5 years, totaling 132 respondents. The respondents were selected using simple random sampling. The analysis includes univariate, bivariate, and multivariate analyses. The findings revealed that more than half of the respondents did not complete their basic immunization (63.2%), and more than half of them had a low level of knowledge (60%). Support from father was also lacking for more than half of the respondents (63.3%), and there were concerns about inadequate sociocultural factors (57.8%). There was a significant relationship between family support, sociocultural factors, and knowledge level with the completeness of basic immunization (P<0.001). The multivariate analysis indicated that having low father support resulted in a 7.3 times higher likelihood of incomplete immunization compared to having high father support. Therefore, the suggestion for this study is to improve not only the knowledge level of mothers but also to increase the knowledge of fathers, so that they can provide full support for their child's health.